Penyuluhan Perawatan Kulit Pada Wanita Lanjut Usia - Saroso, Ade Firman; Sutanto, Hans Utama; Adriani, Donna; Amani, Patwa; Putri, Mustika Anggiane; Imran, Yudhisman; Rachmiyani, Irmiya; Nasution, Dina Putri; Jordhi, Dimas (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2024)
The general aim of this activity is expected to improve the level of public health, especially in Nagrak Village. The specific aim of this activity is to increase elderly women's knowledge about skincare, the participants can carry out skin care independently and appropriately so as to improve skin health and quality of life. The methods used were education about skin care, pretest as initial data to determine knowledge about skincare, and posttest to determine knowledge after being given education. The results of this activity were the mean pretest knowledge about skincare was 1.97 ± 1.07 and the mean posttest knowledge about skincare was 3.1 ± 0.99. Conclusion: elderly women's knowledge increased after being given education. The significance and implications of this activity are that the target is to understand the process of skin aging that occurs due to increasing age as well as good and appropriate care according to the condition of elderly women's skin. Skincare that can be done for elderly women is using sunscreen of at least SPF 30 in outdoor activity, drinking at least 2000 mL of water per day, using facial moisturizer, and cleaning the face with a cleanser containing mineral oil. We consider this theme important because skin health is a reflection of beauty in general and a reflection of health